An efficient MRI agent targeting extracellular markers in prostate adenocarcinoma. Issue 3 (26th September 2018) - Pagoto, Amerigo; Tripepi, Martina; Stefania, Rachele; Lanzardo, Stefania; Livio Longo, Dario; Garello, Francesca; Porpiglia, Francesco; Manfredi, Matteo; Aime, Silvio; Terreno, Enzo
Abstract : Purpose: Prostate cancer (PCa) is the most widespread tumor affecting males in Western countries. We propose a novel MRI molecular tetrameric probe based on the heptadentate gadolinium (Gd)‐AAZTA (6‐amino‐6‐methylperhydro‐1, 4‐diazepinetetraacetic acid) that is able to in vivo detect PCa through the recognition of the fibrin–fibronectin (FB–FN) complex. Methods: The peptide CREKA (Cys‐Arg‐Glu‐Lys‐Ala), targeting the FB–FN complex in the reactive stroma of the tumor, was synthesized by solid phase peptide synthesis (SPPS) and conjugated to the tetramer dL‐(Gd‐AAZTA)4 . The resulting probe was characterized by 1 H relaxometry, tested in vitro on FB clots and in vivo on an orthotopic mouse model of PCa. Results: CREKA‐dL‐(Gd‐AAZTA)4 showed a remarkable relaxivity of 18.2 m M Gd - 1 s−1 (0.47 T, 25°C) because of the presence of 2 water molecules (q = 2) in the inner coordination sphere of each Gd 3+ ion, whose rotational motion (τR ) is lengthened as the result of the relatively high molecular weight. The probe displayed a detectable affinity for plasma‐derived FB clots. On intravenous injection of the probe in an orthotopic mouse model of PCa, a significant increase in the prostate T1 contrast ( 40%) was observed. The MRI signal appears statistically higher either with respect to the one observed for the control probes and to the one detected when CREKA‐dL‐(Gd‐AAZTA)4 was administered to healthy animals. Conclusions: This study demonstrated the ability of the CREKA‐dL‐(Gd‐AAZTA)4 probe to specifically localize in prostate tumor after injection. The high relaxivity of the probe allows the reduction of the injected dose to 20 µmolGd /kg, yielding a good in vivo contrast enhancement in the region of prostate tumor.